Along-Channel Winds in Howe Sound: Climatological Analysis and Case Studies. Issue 1 (1st January 2017) - Bakri, Talaat; Jackson, Peter; Doherty, Ford
ABSTRACT: This paper examines along-channel winds within Howe Sound, British Columbia, Canada, that occur from both the interior plateau out toward the coast as outflows and from the coast inland as inflows. First, the relationships between along-channel winds and pressure, temperature, and humidity are explored in Howe Sound–Cheakamus Valley. The pressure gradients between Pam Rocks and Squamish and Pam Rocks and Pemberton have the strongest correlations with outflow strength and that between Pam Rocks and Squamish has the strongest correlation with inflow strength. Outflows (inflows) have lower (higher) temperatures and dew point temperatures, except for the inflows in summer, which have lower dewpoint temperatures than the overall mean. Second, two case studies of outflow events are presented and described during the period of intensive observations prior to and during the Vancouver 2010 Winter Olympics. The January 2010 outflow event is caused by a zone of strong across-barrier mean sea level pressure gradient. The pressure gradient is formed behind an Arctic front that moved southward across Howe Sound. The February 2010 outflow event is caused by an approaching sea level low pressure centre from the Pacific that formed a northeast–southwest mean sea level pressure gradient across southern British Columbia. In the January case, the outflow layer is about 1.5 km deep, while it is shallower in the February case. Only the January outflow case exhibits hydraulic behaviour.